Kajian Pola Distribusi Hujan Jam-Jaman Di Kabupaten Rokan Hulu Menggunakan Data Satelit Tropical Rainfall Measuring Mission (TRMM) - Solihin, Muhamamad Afdel; Handayani, Yohanna lilis; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Flood calculation design requires an input of rainfall design that is distributed rainfall into hourly rainfall. Distribution of each pattern from a hourly rainfall was necessary to convert rainfall into hourly rainfall designed. Measurement Rainfall data was used utilizing satellite data. The Rainfall data was obtained from Tropical Rainfall Measuring Mission (TRMM) of satellite data. Processed of TRMM data has been done using a Command Prompt software. Data of the Satellite TRMM were extracted by Command Prompt, it was transfered by Zilla File Software which is gsmap. Duration of rainfall into hourly rainfall from 2009 to 2016 was taken one hour until sixty-nine hours. There is incidence of rain with a total of 4001 incidents of rainfall with 22.1228 mm ranifall average, and 839 was the most rainfall incidence in one hour.Keyword: Rainfall distribution, Satellite data, Tropical Rainfall Measuring Mission